Influence of a light-activated glaze on the adhesion of Streptococcus sanguinis to the surface of polymers used in fabrication of interim prostheses - Santos, Daniela Micheline dos [UNESP]; Commar, Betina Chiarelo [UNESP]; Freitas da Silva, Emily Vivianne [UNESP]; Ricardo Barao, Valentim Adelino; Matos, Adaias Oliveira; Goiato, Marcelo Coelho [UNESP] (Wiley-Blackwell, 2019)
Aim This study aimed to investigate the adhesion of Streptococcus sanguinis to the surface of interim prostheses that were treated or not treated with a light-activated glaze, and subjected or not subjected to a thermocycling procedure. Methods 36 specimens of each resin were divided into 4 groups: heat-activated acrylic resin; chemically-activated acrylic resin; bis-acryl composite resin (Protemp; 3M ESPE); and bis-GMA (Charisma; Heraeus Kulzer). Half of the specimens underwent application of glaze and the other half underwent mechanical polishing. Specimens were randomly distributed into groups (N = 9) with and without thermocycling (2000 cycles). Surface energy, roughness and microbiological analyses were performed. Results Groups treated with glaze showed lower roughness when compared with the same groups without glaze treatment, before and after thermocycling, except for the bis-acryl groups after thermocycling. Surface energy values were higher in the groups treated with glaze, except the bis-acryl group before and after thermocycling. After thermocycling, the values of bacterial adhesion decreased numerically, with the exception of the chemically-activated acrylic resin group treated with glaze and the heat-activated acrylic resin group without glaze treatment. Conclusion The application of glaze and the thermocycling do not influence, in a statistically significant manner, the bacterial adhesion on polymer surfaces.
Keywords: acrylic resins; bacterial adhesion; composite resins